Analysis of User Experience in the Design of the AMGM Lab Mobile Application Using the User Experience Questionnaire (UEQ) for Enhanced Efficiency - Ilmiana, Indah Rahma; Ratnasari, Chanifah Indah (Journal of Applied Informatics and Computing, 2024)
AMGM mobile Lab application is a design application supporting documentation of water sample management data. There is a management support system in the form of an intranet. Nevertheless, access to the system is restricted to the office. Naturally, this is less effective since officers must first return to the office in order to enter sample data, and this cannot be done in real-time while they are out in the field. Thus, in order to facilitate these operations, mobile application development is required. User experience analysis is necessary to provide an inventive UX design, which is then required to satisfy laboratory requirements and the company's expectations for the application design. The objective of this study is to use user experience research as a foundation for future application development. In order to do user experience analysis, the User Experience Questionnaire (UEQ) approach is used. The test results reveal that the assessment falls into the excellent category for attractiveness (1.86) and dependability (1.82). The efficiency (1.85) and novelty (1.24) scales are categorized as good. The perspicuity (1.71) and stimulation (1.21) measures are categorized as above average. The mean of the entire scale exceeds 0.8, indicating that people assess all features positively.